WOMEN UNDERREPRESENTATION IN THE AKIMATS OF ASTANA: EXPLORING BARRIERS AND CHALLENGES - Assykpayev, Sanzhar; Ualibek, Aigerim; Bakirova, Bibigul (Nazarbayev University Graduate School of Public Policy, 2024)
Underrepresentation of women in civil service poses a great challenge for the inclusivity, gender equality, and political representation of women’s needs and interests in society. Cultural norms and societal pressures exacerbate the situation further limiting women employee’s career aspirations and advancements. In the presence of systematic barriers perpetuating underrepresentation, promotion of policies that encourage women’s participation are found to be an effective solution. This work explores the reasons and factors behind the underrepresentation of women in local governments through a qualitative case study of several akimats of Astana city. By interviewing representatives from local municipalities research reveals emerging themes from the experiences and challenges women employees face during their work and advancement to decision-making positions. Results of the study indicate that societal and cultural biases are prominent reasons behind the underrepresentation of women in akimats. Systematic pressure built on the base of male preference and historically developed assigned roles for women was found to be significant in defining the barriers women face during promotion to decision-making positions. Additionally, the study underlines the importance of domestic responsibilities in evaluating factors that influence women’s decision to pursue political careers in Astana akimats.
Недостаточное представительство женщин в акиматах Астаны: исследование преград и вызовов
Астана әкімдіктерінде әйел мамандарының аздығы: кедергі мен мәселелерді зерттеу
Keywords: Type of access: Open access; Underrepresentation; Stereotypes; Akimat; Domestic responsibilities; Workplace Inequality; Astana; Women professionals